"New normal" no more: democratic backsliding in Singapore after 2015. Issue 7 (2nd October 2020) - Abdullah, Walid Jumblatt
ABSTRACT: After the "watershed" General Elections (GE) in 2011, Singapore seemed primed for greater democratization. The ruling People's Action Party (PAP) adopted a softer tone, and promised an expansion of the political space. Yet, after the subsequent GE in 2015, in which the PAP attained a much higher share of the votes in a resounding victory, there is an apparent democratic backsliding. Academics have been publicly censured by state leaders, legislation has been passed to strengthen the coercive capacity of the state, and dissenters have faced draconian measures. This paper investigates the reversal of democratization in Singapore, post-2015. I contend that after garnering a high level of political capital in GE 2015, the PAP reverted to its more familiar authoritarian stratagem. This was possible because of two main reasons: (1) the absence of a strong and coherent opposition which has enough credibility with the voters to cause a serious dent in the PAP's electoral success; and (2) the absence of genuine reformers within the party to push through the agenda of democratization. Comparisons with Malaysia and the recent success of the opposition in a similar political system will be made. Broader lessons on the conditions under which authoritarianism is strengthened will also be noted.